Effect of microwave disinfection on the surface roughness of three denture base resins after tooth brushing - Izumida, Fernanda Emiko [UNESP]; Ribeiro, Roberta Chuqui [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2011)
Objective: This study investigated the effect of microwave disinfection on the roughness of three heat-polymerised acrylic resins after tooth brushing. Background: Microwave disinfection has been recommended to reduce cross-contamination. However, this procedure may also influence the physical and mechanical properties of acrylic resins. Materials and methods: Specimens (40 x 20 x 2 mm) of resins: Lucitone 550 (L), QC 20(QC) and Acron MC (A) were prepared and divided into four groups (n = 10): Control groups 1 (C1) and 2 (C2) stored in water for 48 h or 7 days; Test groups 1 (MW2) and 2 (MW7) stored in water for 48 h and disinfected (650 W for 6 min) daily for 2 or 7 days, respectively. After treatments, the specimens were placed in a tooth brushing machine at a rate of 60 reciprocal strokes per minute. The specimens were brushed with 20 000 strokes, which represent approximately 2 years of denture cleansing. The surface roughness (Ra) was evaluated before and after the tooth brushing. Data were analysed by two-way anova and Tukey Honestly Significant Difference (HSD) post hoc tests (alpha = 0.05). Results: The data revealed significant changes between test groups for A and L resins. Comparison among resins revealed that for MW7, the roughness of A was significantly lower than that of L. After the seven microwave cycles, it could be seen that the roughness values of QC were significantly lower than those of L. Conclusions: The roughness of QC after brushing was not significantly affected by microwave disinfection. For A and L, seven microwave cycles resulted in increased roughness.
Keywords: acrylic resins; tooth brushing; abrasion; microwave disinfection